The Forsyte Saga, Volume I. : The Man Of Property - Galsworthy, John, 1867-1933 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Forsyte Saga, Volume I" by John Galsworthy is a series of three novels and two interludes published between 1906 and 1921. The work chronicles an upper-middle-class English family keenly aware of their "new money" status. At its center is Soames Forsyte, a solicitor who views himself as a "man of property" through his accumulation of possessions$1 (Bincluding his beautiful wife Irene. His obsessive desire to own and control leads to jealousy, forbidden love, and tragic consequences that ripple across generations, entangling his daughter and cousin in the family's troubled past. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Forsyte_Saga
Release date is 2006-06-14
Produced by David Widger
Keywords: England -- Social life and customs -- 19th century -- Fiction; Domestic fiction; Women -- England -- Fiction; Middle class -- England -- Fiction; England -- Social life and customs -- 20th century -- Fiction; Forsyte family (Fictitious characters) -- Fiction; Families -- England -- Fiction